2012
DOI: 10.24926/iip.v3i1.249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Consumer-Generated Marketing Plan for Medication Therapy Management Services

Abstract: We greatly appreciate the assistance of Marj Schneider and her colleagues at Tybee Types during the focus group transcription process.The authors gratefully acknowledge Dr. Serguei Pakhomov for expert consultation during natural language processing analysis. Declarations and Disclosures:The authors declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…6 Before data collection, pharmacists at participating locations were trained on MTM delivery and use of the promotional approach assigned to their site. Pharmacists providing verbal promotional messages (telephone calls or face-to-face) received a brief script to follow with the patient and a list of follow-up points and questions for use if the patient was not immediately interested.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Before data collection, pharmacists at participating locations were trained on MTM delivery and use of the promotional approach assigned to their site. Pharmacists providing verbal promotional messages (telephone calls or face-to-face) received a brief script to follow with the patient and a list of follow-up points and questions for use if the patient was not immediately interested.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have described the importance of clearly explaining the purpose of MTM, exhibiting a team-based approach to care, explaining why the pharmacist is the optimal health care provider to provide MTM, focusing on those services patients perceive as most beneficial (such as the personal medication list), using patient-friendly language (i.e., "medication check-up" and "medication management"), and increasing overall exposure to MTM. [5][6][7] Although these studies have identified patient preferences for marketing techniques, no studies to date have been conducted to implement these strategies in a prospective, randomized way.…”
Section: [Text Begins]mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that patients and pharmacists have different perceptions of the pharmacist's role in healthcare, with patients primarily seeing pharmacists as dispensers of medicine. [11][12][13][14][15][16] This is to be expected since community pharmacists, the most publicly visible, operate under a retail business model, in which production processes revolve around the sale of merchandise. 17 In the retail business model, success or failure of community pharmacies depends on the sale of tangible goods such as nonprescription drugs, prescription medicines, medical devices, durable medical equipment, and adherence packaging.…”
Section: Product As a Tangible Objectmentioning
confidence: 99%
“…Applying the principles of service design can help pharmacists manage both the quality and patient perceptions of the service provided [7,8]. Service design is the process of planning and organizing the customer service experience using a number of methods and tools derived from disciplines as diverse as ethnography, systems engineering, management science, and informatics.…”
Section: Challenges In Marketing Pharmacy Servicesmentioning
confidence: 99%